Optimization of fuzzy linear fractional programming problem with fuzzy numbers - Sapan Das (Big Data and Computing Visions)
In this paper, we consider a Fuzzy Linear Fractional Programming (FLFP) problem under the condition that the objective function and the values of the right-hand side are represented by symmetric trapezoidal fuzzy numbers while the left-hand side constraints are represented by real numbers. Decision variables are characterized by trapezoidal fuzzy numbers and non-negative numbers. Utilizing the ranking function and computation of trapezoidal fuzzy numbers, the FLFP problem is transformed into a Crisp Linear Fractional Programming (CLFP) problem. This paper outfits another idea for diminishing the computational complexity, in any case without losing its viability crisp LFP problem. A modified possibility programming problem, Swarup is utilized to solve this program. Lead from real-life problems, a couple of mathematical models is considered to survey the legitimacy, usefulness and applicability of our method. Finally, some mathematical analysis along with one case study is given to show the novel strategies are superior to the current techniques.